Economia da educação, inovação tecnológica e o conceito de capital humano - Guimarães, André Sathler [UNESP]; Pires, Valdemir Aparecido [UNESP] (My University, 2011)
The paper shows the basic economic theories that support the rationality behind the financial and technological dominance in present social relations, and try to demonstrate the paradoxes and contradictions of the theoretical system, having as background elements from the Frankfurt School. From the field of theoretical economics of education, authors discuss the concept of human capital with its economical dimensions, presenting their affinities and disparities with Keynesians, neoclassical economics and the evolutionary economics of Schumpeter.

Identificam-se as teorias econômicas fundadoras dos argumentos que sustentam a racionalidade justificadora do predomínio financeiro-tecnológico nas relações sociais atuais, submetendo-as ao crivo da crítica emanada da Escola de Frankfurt. No campo teórico da economia da educação, discute-se o conceito de capital humano a partir de suas dimensões econômicas, apresentando suas afinidades e contradições com as linhas de pensamento keynesiana, neoclássica e da economia evolucionista schumpeteriana
Education economy, technological innovation and the concept of human capital
Keywords: Education economy; Human capital; Economia da educação; Capital humano